2009
DOI: 10.1107/s160053680903894x
|View full text |Cite
|
Sign up to set email alerts
|

N′-[(E)-3-Pyridylmethylidene]benzohydrazide

Abstract: The title compound, C13H11N3O, was prepared by the reaction of benzohydrazide and nicotinaldehyde. The dihedral angle between the planes of the two aromatic rings is 47.78 (9)°. The crystal structure is stabilized by inter­molecular N—H⋯N hydrogen-bonding inter­actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The benzene ring is inclined to the pyridine ring by 5.7 (2)°. All the bond lengths are comparable with those observed in similar Schiff bases reported on previously (Wen et al, 2009;Mohd Lair et al, 2009;Sun et al, 2009).…”
Section: Sup-1supporting
confidence: 90%
“…The benzene ring is inclined to the pyridine ring by 5.7 (2)°. All the bond lengths are comparable with those observed in similar Schiff bases reported on previously (Wen et al, 2009;Mohd Lair et al, 2009;Sun et al, 2009).…”
Section: Sup-1supporting
confidence: 90%
“…This intermolecular interaction is stabilizing in Curcumin. The bond lengths of C=O are lengthened in dimer optimization [26]. To find the most optimized geometry, the energy calculations are carried out for various possible conformers are listed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The systematic comparison of the results from DFT theory with results of experiments has shown that the method using B3LYP functional is the most promising in providing correct vibrational wave numbers. The calculated geometrical parameters were compared with X-ray diffraction result [22]. Normal coordinate analyses were carried out for the title compound to provide a complete assignment of fundamental frequencies.…”
Section: Computational Detailsmentioning
confidence: 99%